2013
DOI: 10.1002/jmri.24311
|View full text |Cite
|
Sign up to set email alerts
|

MRI of knee ligament injury and reconstruction

Abstract: Knee ligament instability may lead to meniscal and chondral damage, resulting in early osteoarthritis. Due to its superior soft tissue contrast and avoidance of harmful ionizing radiation, MRI has become the most important imaging modality for early recognition of structural defects of the knee joint. This review aims to the understanding of MRI appearances of knee ligament structures associated with knee instability, and to review the common patterns of altered knee mechanics that lead to ligament failure. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 97 publications
1
21
0
1
Order By: Relevance
“…Recently it has been noted that the anatomic graft location affects the signal properties of the graft so that the increased graft SI is seen for a prolonged period. 17 This is a finding similar to that in our study, with more than half of the PL grafts having increased SI. Based on our results, an increased graft SI can be frequently seen with no association to knee laxity 2 years after DB ACL reconstruction.…”
Section: Discussionsupporting
confidence: 88%
“…Recently it has been noted that the anatomic graft location affects the signal properties of the graft so that the increased graft SI is seen for a prolonged period. 17 This is a finding similar to that in our study, with more than half of the PL grafts having increased SI. Based on our results, an increased graft SI can be frequently seen with no association to knee laxity 2 years after DB ACL reconstruction.…”
Section: Discussionsupporting
confidence: 88%
“…Farshad-Amacker et al observed that recent trend toward "anatomic" femoral and tibial footprints affects signal properties of the graft (22). They described prolonged hyperintensity in the delayed perioperative period, however uncertain if IGSI is due to plastic deformation or higher tension of the graft (22). Our results suggest there appears to be a difference in IGSI between the tibial and femoral tunnel, which may be attributed to the femoral tunnel positioning and graft fixation.…”
Section: Discussionmentioning
confidence: 56%
“…In the setting of a severe PLC injury, the adjacent peroneal nerve should be assessed for the presence of traumatic neuritis or disruption of nerve fascicles [ 14 ]. Halinen et al [ 15 ] demonstrated that MRI (1.5 T) ability to detect lateral meniscal tears was less than hoped, but medial meniscal tears, ligamentous injuries, and bone bruises were seen more precisely in 44 cases of multiligament knee injury.…”
Section: Mrimentioning
confidence: 98%